Cyclic Pseudo-Fusion in a Dual-Chamber Pacemaker - Chemello, Diego; Subramanian, Anandaraja; Glover, Benedict; Watkins, Sheila; Cameron, Douglas (Clinical and Biomedical Research, 2010)
Studies have shown that avoidance of right ventricular pacing results in a decrease in the incidence of atrial fibrillation and congestive heart failure. Newer algorithms which promote intrinsic conduction and decrease the frequency of ventricular pacing have been developed. However some of these new pacing algorithms are complex and can create potential pitfalls for the clinician. Additionally, these features may not be applicable to a reasonable amount of patients. We describe an example of a pacemaker pseudo-malfunction caused by one of these new algorithms.